A new heuristic-based bi-objective simulated annealing method for U-shaped assembly line balancing. (2016) - Fathi, Masood; Álvarez, María Jesús; Rodríguez, Victoria
The U-shaped assembly line has received a considerable attention and has been widely used in industry in recent years due to the pressures of the just-in-time (JIT) manufacturing philosophy. However, balancing the U-shaped line is more difficult than balancing the traditional straight line. This study aims at balancing the U-shaped assembly line by introducing a novel heuristic which is based on the simulated annealing (SA) algorithm. The objectives to be optimised in this study are the number of workstations and balance efficiency. The performance of the proposed algorithm is examined by solving a set of standard test problems and a real case study. The results attained by the proposed algorithm were compared against the best known solution in the literature and it was found that the proposed algorithm is able to find good solutions in a reasonably short computational time. [Received 29 December 2012; Revised 28 March 2014; Revised 25 August 2014; Revised 22 May 2015; Accepted 26 May 2015]